Стимуляція протипухлинним препаратом таксолом клітинного циклу (G1/S перехід) в клітинах анапластичного раку щитовидної залози - Тронько, М.Д.; Пушкарьов, В.В.; Ковзун, О.І.; Пушкарьов, В.М. (Видавничий дім "Академперіодика" НАН України, 2007)
The effect of antitumor drug, taxol, on the activity of cell cycle regulatory factors in two cell lines of anaplastic thyroid cancer ARO and KTC-2 is studied. It is shown that taxol enhances the phosphorylation of retinoblastoma protein, pRB, in both cell lines. The taxol addition to the incubation medium in 6 h of incubation induced a significant decrease of the level of the inhibitor of cyclin-dependent kinases (CDK) and G1/S progression — р27KIP1. The level of another CDK inhibitor, p21waf1, was also decreased but after 12 h of incubation. These results indicate that the low concentration of taxol stimulates the early cell cycle stages in thyroid anaplastic cancer cells.